2012
DOI: 10.1515/hsz-2012-0145
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and metabolism of astroglia-rich primary cultures from cathepsin K-deficient mice

Abstract: Cathepsin K is important for the brain, because its deficiency in mice is associated with a marked decrease in differentiated astrocytes and changes in neuronal patterning in the hippocampus as well as with learning and memory deficits. As cathepsin K activity is most prominent in hippocampal regions of wild type animals, we hypothesised alterations in astrocyte-mediated support of neurons as a potential mechanism underlying the impaired brain functions in cathepsin K-deficient mice. To address this hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“… 19 Similar results have been reported for the cysteine cathepsin L by Strojnik and co-workers 47 , showing high cathepsin L expression in astrocytomas and GBM, but these high levels were not predictive. We have also shown that cathepsin K is expressed in normal brain cells as has been reported for all brain regions of wild type mice 48 where it has been associated with neurobe-havioral disorders such as schizophrenia. 49 At the protein level, cathepsin K was detected in vesicles of neuronal and non-neuronal cells throughout the mouse brain and its deficiency was associated with a marked decrease in differentiated astrocytes, indicating a possible role of cathepsin K in stem cell differentiation.…”
Section: Discussionsupporting
confidence: 76%
“… 19 Similar results have been reported for the cysteine cathepsin L by Strojnik and co-workers 47 , showing high cathepsin L expression in astrocytomas and GBM, but these high levels were not predictive. We have also shown that cathepsin K is expressed in normal brain cells as has been reported for all brain regions of wild type mice 48 where it has been associated with neurobe-havioral disorders such as schizophrenia. 49 At the protein level, cathepsin K was detected in vesicles of neuronal and non-neuronal cells throughout the mouse brain and its deficiency was associated with a marked decrease in differentiated astrocytes, indicating a possible role of cathepsin K in stem cell differentiation.…”
Section: Discussionsupporting
confidence: 76%
“…Because of its involvement in pycnodysostosis [51], osteoporosis [52], [53] and invasive carcinomas and their metastasis, a series of small inhibitory compounds have been developed for clinical application [53]. CatK knockdown animals show considerable neural defects indicating its role in normal brain functioning [54], [55], which is in contrast to CatB or CatL-deficient animals [56], although in CatB −/− and CatL −/− double knock-out mice, brain atrophy due to massive apoptosis of neurons is lethal [52]. In astroglia-rich primary cultures from CatK-deficient mice it appeared that CatK plays a role in differentiation of oligodendrocytes [52].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that diabetes may potentiate cathepsin K expression. Moreover, cathepsin K deficiency in mice is associated with a marked decrease in differentiated astrocytes and learning and memory deficits [48]. Sema3A is also positively involved in the regulation of the central and peripheral nervous systems.…”
Section: Discussionmentioning
confidence: 99%